Expression, polymorphism analysis, reticulocyte binding and serological reactivity of two Plasmodium vivax MSP-1 protein recombinant fragments (2003)
Among the four parasite species causing malaria in humans, Plasmodium vivax prevails on both the Asian and the American continents. Several antigens from this parasite’s erythrocytic stages have been characterised and some of them are considered to be good vaccine candidates. The P. vivax merozoite surface protein-1 (PvMSP-1) is a 200 kDa antigen, thought to mediate the initial contact between the merozoite and the erythrocyte. An effective blockage of this interaction could be important in anti-malarial vaccine design. This study analyses the genetic polymorphism, binding to both reticulocytes and erythrocytes, antigenicity and immunogenicity of two recombinant proteins belonging to the 33 kDa PvMSP-1 proteolytic fragment. Both regions showed very low genetic variation, bound reticulocytes with higher affinity than erythrocytes, were recognised by naturally P. vivax-infected patient sera and were immunogenic when used to immunise rabbits, making them good vaccine candidates against P. vivax, to be further preclinically tested in the Aotus monkey model.